PRAKTIK KOMUNIKASI ANTARBUDAYA PADA MAHASISWA EKSPATRIAT DALAM PROGRAM BAHASA INDONESIA UNTUK PENUTUR ASING (BIPA) - Anindita Anindita; Novica Woelandari (Jurnal Pustaka Komunikasi, 2020)
Language is one of cultures that cannot be separated from human life. Indonesian language studied by expatriate students in the BIPA program becomes a bridge and a means of communication that can produce interaction between foreign students who have different cultures. However, as Indonesian Language learners, expatriate students from various countries certainly experience obstacles in communication. This study aims to find out more about intercultural communication practices among expatriate students in the Indonesian Language for Foreign Speakers (BIPA) program at the International Language Institute, Faculty of Cultural Sciences, University of Indonesia. The research method used in this research is descriptive qualitative, using a post-positivistic paradigm in which the data obtained in this study are through interviews and participant observation. Interviews were conducted with four informants from different countries representing the majority and minority countries. The results showed that in the practice of intercultural communication, students used a lot of primary communication patterns, where students used verbal and non-verbal symbols, and secondary communication patterns, where students used tools / media that helped the communication process such as the use of dictionaries and Google Translate. In this study also found that students experience various cultural phenomena including cultural adaptation, acculturation, assimilation, and culture shock.